3x*3x-2x+7=0

Simple and best practice solution for 3x*3x-2x+7=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*3x-2x+7=0 equation:


Simplifying
3x * 3x + -2x + 7 = 0

Reorder the terms for easier multiplication:
3 * 3x * x + -2x + 7 = 0

Multiply 3 * 3
9x * x + -2x + 7 = 0

Multiply x * x
9x2 + -2x + 7 = 0

Reorder the terms:
7 + -2x + 9x2 = 0

Solving
7 + -2x + 9x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
9 the coefficient of the squared term: 

Divide each side by '9'.
0.7777777778 + -0.2222222222x + x2 = 0

Move the constant term to the right:

Add '-0.7777777778' to each side of the equation.
0.7777777778 + -0.2222222222x + -0.7777777778 + x2 = 0 + -0.7777777778

Reorder the terms:
0.7777777778 + -0.7777777778 + -0.2222222222x + x2 = 0 + -0.7777777778

Combine like terms: 0.7777777778 + -0.7777777778 = 0.0000000000
0.0000000000 + -0.2222222222x + x2 = 0 + -0.7777777778
-0.2222222222x + x2 = 0 + -0.7777777778

Combine like terms: 0 + -0.7777777778 = -0.7777777778
-0.2222222222x + x2 = -0.7777777778

The x term is -0.2222222222x.  Take half its coefficient (-0.1111111111).
Square it (0.01234567901) and add it to both sides.

Add '0.01234567901' to each side of the equation.
-0.2222222222x + 0.01234567901 + x2 = -0.7777777778 + 0.01234567901

Reorder the terms:
0.01234567901 + -0.2222222222x + x2 = -0.7777777778 + 0.01234567901

Combine like terms: -0.7777777778 + 0.01234567901 = -0.76543209879
0.01234567901 + -0.2222222222x + x2 = -0.76543209879

Factor a perfect square on the left side:
(x + -0.1111111111)(x + -0.1111111111) = -0.76543209879

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 6-3-(-10)-7+(-13)+33= | | 58(w)(w+8)=x | | (3x-5)(x-2)=0 | | 8-5x-x=14 | | (8x-5x)+(-2-8)= | | X+(3-2x)= | | -3/4+4/-7= | | 3/4+4/7= | | -3/4+-4/7= | | 3x+4y=a | | 10x^3-7x^2-12x=0 | | 3x+12=9x+36 | | 3x+12=9x+39 | | 2(3x+4)-1=9 | | 2x+13=7x+5 | | (x+5)*(x+5)=6 | | 6x+3=7x+2 | | 7+2a=33-2a | | =x^2+3xy+2y^2 | | sqrt(5x+5)=4 | | 2x+4X-4=16 | | 3000*x=7000 | | -2-28= | | (5-v)(4v-7)=0 | | v^2-v-30=o | | .67(1+n)=-.5n | | (3v+8)(2-v)=0 | | x^4-14x^2+24x-10=0 | | 4a-8a+10=4 | | 13x-4=5x+32 | | 25.12=.3333(12.56h) | | -6a+8= |

Equations solver categories